Growth and Poverty Alleviation: Lessons from Development Experience - T. N. Srinivasan (Asian Development Bank Institute (ADBI), 2001)
Poverty is a multifaceted phenomenon that goes beyond lack of adequate income. The overarching objective of development in many countries has been and continues to be the eradication of all facets of poverty. Rapid as well as well equitable growth in income has always been viewed as aninstrument for achieving this objective. Although only a few developing countries have succeeded insustaining rapid growth for a long period and in reducing poverty significantly, the evidence does suggest an association between episodes of rapid growth and poverty reduction. Policies and processes can be identified a priori, some of which would be expected to generate sustained growth and poverty reduction while others either would not lead to growth or to poverty reduction. The interesting and important analytical issue is why we see the former set ofpolicies and processes only in a few countries. In analyzing this issue, it is clear that a comparative (across nations, sub-national units and time spans) framework is most appropriate.
hdl:11540/4122
Keywords: 330